International Entrepreneurship as Development of Entrepreneurship Education: A Study Case of ASEAN Economic Community Countries - Dotty Wimpertiwi (The Winners, 2018)
The objectives of this research were; (1) adding up the enrichment in the entrepreneurship education in BINUS to change the mindset of the students to be able to compete and create the new workspace in the AEC, especially in three countries (Indonesia, Malaysia, and Singapore) using PEST analysis to understand more about how doing entrepreneurship global or international. (2) Giving the contribution to enrich the knowledge of the basic concept of AEC for entrepreneur students. (3) Providing the insight on the challenge and the opportunity especially in International Entrepreneur. The research methods were qualitative and descriptive analysis follow by literature study. Results show that by learning entrepreneurship of ASEAN will change the mindset of the students to be more competing when doing business. There are several opportunity and challenge in neighboring countries between the member of the AEC, for the university that has the start-up or SMEs for being global or international.